Description of Pain and Fatigue Problems in the Elderly with Self Care Deficits: Bathing - Rina Anggraeni; Fitriani Rahmawati; Novi Indrayati; Qurrotul Aeni; Andriyani Mustika Nurwijayanti (Global Health Science Group, 2021)
Elderly experience decreased body function causing them to experience deficit in self-care. Self-care deficit: Bathing is caused by several factors including pain and physical weakness. The purpose of this study was to describe the problem of pain and physical weakness in the elderly who experience a Self-Care Deficit: Bathing in Balok Village, Kendal District. This research design is a descriptive study of quantitative research type with a survey approach. The sample in this study amounted to 52 respondents with a total sampling technique. Measuring instruments in the form of a questionnaire Numerical Rating Scale (NRS) for pain and a Fatique Assessment Scale (FAS) for fatigue and that has been standard. Data analysis using univariate. The results showed that the pain in the elderly with Self-Care Deficits: Bathing was painless 16 (30.8%), mild pain 11 (21.2%) moderate pain 19 (36.5%) and severe pain 6 (11.3%). Physical weakness in the elderly: not fatique or normal 47 (90.4%) fatique 5 (9.6%).